The Oxygen project: a prospective study to assess the effectiveness of a targeted intervention to improve oxygen management in hospitalised patients. Issue 5 (27th May 2021) - Nguyen, Benjamin; Gunaratne, Yodithya; Kemp, Teresa; Chan, Wei; Cochrane, Belinda
Abstract: Background: Oxygen is commonly used in the acute care setting. However, used inappropriately, oxygen therapy can result in adverse consequences, including progressive respiratory failure and death. Aim: To investigate the effectiveness of a targeted intervention to improve prescribing practice and therapeutic application of supplemental oxygen. Methods: Respiratory, Oncology and Surgery wards were targeted for the intervention. Nursing and junior medical staff from these wards undertook an education programme about safe use of oxygen. Cross‐sectional data about oxygen prescribing, administration and monitoring were collected on inpatients in these wards at baseline, and at 3 and 6 months post‐intervention, using a modified version of the British Thoracic Society Oxygen Audit Tool. Results: At baseline, there was a written prescription for oxygen in 56% of patients ( n = 43) using oxygen and this increased to 75% ( n = 44) at 3 months, and remained at 65% ( n = 48) at 6 months. However, the increased prescription rates were not statistically significant when compared to baseline ( χ 2 = 3.54, df = 1, P = 0.06 and χ 2 = 0.73, df = 1, P = 0.40, respectively). The observed increase in oxygen prescriptions was driven by the medical wards: Oncology ward at 3 months ( χ 2 = 8.24, df = 1, P = 0.004); and Respiratory ward at 3 months ( χ 2 = 3.31, df = 1, P = 0.069) and 6 months ( χ 2 = 4.98, df = 1, P = 0.026). Conclusion: The education programme intervention to improve oxygen prescription showed promise in the medical wards but did not impact outcomes in the surgical ward setting, where different strategies may be needed.